1996
DOI: 10.1128/jvi.70.4.2101-2106.1996
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell lymphotropic virus type 1 Tax mediates enhanced transcription in CD4+ T lymphocytes

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is the etiologic agent of adult T-cell leukemia/lymphoma and is associated with a variety of immunoregulatory disorders. HTLV-1 has been shown to bind to and infect a variety of hematopoietic and nonhematopoietic cells. However, both in vivo and in vitro, the provirus is mostly detected in and preferentially transforms CD4 ؉ T cells. The molecular mechanism that determines the CD4 ؉ T-cell tropism of HTLV-1 has not been determined. Using cocultures of purified CD4 ؉ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 56 publications
(48 reference statements)
2
18
0
Order By: Relevance
“…To obtain resting cells, PBMC were cultured for 48 hr in RPMI 1640 supplemented with 10% fetal bovine serum, 0.3 mg/ml Lglutamine, 100 U/ml penicillin and 100 mg/ml streptomycin (complete medium) at 37°C in 7% CO 2 . Cells were stimulated using 5 U/ml rIL2 (Boehringer Mannheim Biochemical, Indianapolis, IN) and 2.5 g/ml phytohemagglutinin P (PHA P) (activation medium) and were maintained in stimulation medium for the indicated times [Newbound et al, 1996].…”
Section: Materials and Methods Cells And Culturementioning
confidence: 99%
See 2 more Smart Citations
“…To obtain resting cells, PBMC were cultured for 48 hr in RPMI 1640 supplemented with 10% fetal bovine serum, 0.3 mg/ml Lglutamine, 100 U/ml penicillin and 100 mg/ml streptomycin (complete medium) at 37°C in 7% CO 2 . Cells were stimulated using 5 U/ml rIL2 (Boehringer Mannheim Biochemical, Indianapolis, IN) and 2.5 g/ml phytohemagglutinin P (PHA P) (activation medium) and were maintained in stimulation medium for the indicated times [Newbound et al, 1996].…”
Section: Materials and Methods Cells And Culturementioning
confidence: 99%
“…For the RNase protection assay a plasmid called pCRJL5, containing the full length human ICER II gene, was a generous gift from Dr. J. Habener and has been previously described [Bodor et al, 1996]. For transient transfections a HTLV-1 LTR and LTR-Tax plasmids have been previously described [Newbound et al, 1996]. A CMV-driven ICER II␥ plasmid was a generous gift from Dr. C. Tinti and has been previously described [Tinti et al, 1996].…”
Section: Plasmid Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of transduction was confirmed by fluorescence microscopy. A luciferase reporter assay was used as described previously [24,32] to confirm the ability of the recombinant Tax2 proteins to regulate viral transcription.…”
Section: Cellular Treatment With Extracellular Tax Proteins or Transdmentioning
confidence: 99%
“…Such observations indicate that the viral receptor is present on many cells types, as con-firmed by binding studies and pseudotype interference assays. They in turn indicate that the in vivo CD4 ϩ T-cell tropism of HTLV-1 is determined mainly at a postpenetration step of the retrovirus life cycle (34). In contrast to the wide host range of cells susceptible to HTLV-1 infection, we have repeatedly observed that Jurkat or CEM T cells were unable to sustain a productive infection after coculture with irradiated HTLV-1producing cells.…”
mentioning
confidence: 90%